Effect of hydrothermal synthesis duration on the properties oftransparent conductive coatings based on zinc oxide - Мукaш Ж.О.; Сaитовa Н.К.; Гриценко, Л.В.; Кaлкозовa Ж.К.; Кумеков, С.Е.; Aбдуллин Х.А. (Recent Contributions to Physics, 2016)
The parameters of the hydrothermal synthesis to obtain a ordered growth of layers containing nanorods arrays, and solid homogeneous films of boron (BZO) or aluminium (AZO) doped zinc oxide were determed. The morphology, optical, electrical and photoluminescent properties of thin films based on zinc oxide, synthesized by low cost hydrothermal method, in dependence on conditions of hydrothermal route and subsequent thermal treatments were investigated. Research results showed that obtained samples are continuous films of closely packed rods, fused at the bottom with the hexagonal structure, oriented perpendicular to the growth surface. The electrical characteristics, such as concentration, mobility and resistivity of these samples were investigated by Hall effect measurement van der Pauw configuration contacts. Heat treatment in a vacuum at a temperature of 450 °C for 1 hour improved the conductivity of the synthesized thin films.